The Relationship between Phytoplankton Diversity and Water Quality of Kalimati Pamarayan River, Serang Regency, Banten Province - Imandhani, Arnaufalino; Nurdin, Hery Sutrawan; Aryani, Desy (Agrikan Jurnal Agribisnis Perikanan, 2024)
Phytoplankton is a biological parameter that can be used as an indicator to evaluate the quality and fertility level of water. Phytoplankton is also the largest contributor of oxygen in the waters because of the role of phytoplankton as the initial binder of solar energy. This study aims to identify phytoplankton diversity, analyze water quality, analyze the relationship between phytoplankton diversity and water quality of Kalimati Pamarayan river, Serang Regency, Banten Province. The study was conducted in August-September 2023. Sampling was carried out 2 times, namely in rainy and sunny conditions, with 3 repeats. The methods used in this study are survey methods and location determination by purposive sampling method. The data obtained is then analyzed in Microsoft Excel. The results showed that the quality of Kalimati river water in terms of physicochemical parameters is still mostly in the number of levels in accordance with water quality standards according to PP no 21 of 2021. Five classes of phytoplankton were found in two samples in two different conditions: Bacillariophyceae, Cyanophyceae, Chlorophyceae, Charophyceae, and Euglenaphyceae. The diversity and uniformity index of most stations obtained moderate to high score results. The results of the dominance index show that there are no types of phytoplankton that dominate in the Kalimati river.